A comparison between static load test and high strain dynamic test on bored piles - Murugun @ Arokiasamy, Michael Angelo (2006)
Piles are both statically and dynamically tested to obtain the capacity and to verify design. Both the test will provide results that may vary base on the method applied in conducting the test. It is therefore, necessary to compare the results of a static load test with dynamic load test. Many comparison studies are conducted worldwide, but most of it is for displacement pile. Therefore, the results of the test are compared for replacement piles. The piles are tested statically prior to dynamic test. The test results shows that a good agreement have achieved between both the test with plus minus 2mm at working load in terms of settlement. Comparatively the settlement predicted in dynamic load test is smaller compared to static load test. In terms of total capacity, the Davisson’s method gives the lowest value compared to other methods. The Davisson’s method is used to compare the results because it is more conservative. The comparison shows that the piles are within 20% relative to the capacity obtained through Davisson’s method. Since the static test was conducted prior to dynamic test, the capacity obtained from dynamic test is higher due to the pile undergone elastic compression during static load test and also due to soil setup. The shaft distribution show that large shaft distribution obtained on long piles. They are comparable with the dynamic test taking into account the time factor